Psychometric properties of the Compass of Shame Scale: Testing for measurement invariance across community boys and boys in foster care and juvenile detentions facilities - Vagos, Paula (2021)
Background Shame has been found to relate to several psychopathologies, but the way the individual copes with experiences of shame may determine specifc expressions of psychopathology, making it essential to rigorously address such coping styles. Objective This study evaluated the psychometric properties of a Portuguese version of the Compass of Shame Scale using an adolescent sample, to investigate if its internal structure was valid for diverse adolescent subsamples, and to gather evidence on the construct validity of the instrument. Method Adolescent community boys and girls (n=1924; 52.3% boys) and adolescent boys with a history of behavior problems taken from foster care and juvenile detention facilities (n = 396) flled in self-report questionnaires on coping with shame and other relevant constructs. Results A fve-factor model was applicable to exploring the coping with shame of adolescent community boys and girls and adolescent boys with behavior problems. Girls, in comparison with boys, more frequently internalized shame or coped with it adaptively. Boys taken from foster care and juvenile detention facilities, compared with community boys, more often externalized shame by attacking others and less frequently attacked themselves, avoided shame experiences or coped with it adaptively. Construct validity in relation to self-criticism, external shame, and experiential avoidance was found. Conclusions The measure demonstrated reliability and validity estimates consistent with expectations across diverse samples of adolescents. So, it may help advance knowledge on how diverse youth cope with shame and on the interchanges between experiencing shame, managing shame, and psychopathology.